PENDAMPINGAN KELOMPOK USAHA SAMILER DI DESA PURWOASRI KECAMATAN SINGOSARI KABUPATEN MALANG UNTUK MENINGKATKAN MUTU KEMASAN DAN PEMASARAN - Wahyu H, Tri Asih; Lestari, Purwaning Budi (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2018)
Mrs. Artiyam, Mrs. Suparmi, and Srikandi Women's Cooperative are partners involved in Community Partnership Program activities living in Purwoasri Village, Singosari Sub-district, Malang Regency. Mrs. Artiyam and Mrs. Suparmi are small-scale household entrepreneurs/crackers. Mrs. Artiyam and Mrs. Suparmi and Srikandi Women's Cooperative sell samiler crackers produced by Mrs. Artiyam and Mrs. Suparmi. Women's Cooperative Srikandi sell crude samiler crackers and there is no packing, so far only limited to crackle bags so it is less attractive, besides there is no online marketing because they do not have the skills to utilize IT. The solution to this problem is the training of packaging design to create an attractive packaging design and increase the selling value; training Use of IT for online marketing. With the presence of training and assistance, partner skills on the packaging of products and marketing increase and increase turnover.